Prone positioning in awake patients as part of treatment in patients with COVID-19 pneumonia (Actualizaciones en Sida e Infectología, 2021)
The prone positioning (PP) in awake patients is one of the tools to reduce the number of admissions to Intensive Care Unit (ICU) in cases of Covid-19 hipoxemic pneumonia. Some patients do not tolerate PP (intolerants) and others that tolerate it do not respond with improvement of PO2 or oxygen saturation. We present here a series of 34 patients who underwent PP. Eighteen of them tolerated PP (52,9%). Nine patients (26,4%) were admitted to ICU: 7 who had not tolerated PP (43,7%) and 2 who had tolerated PP (11,1%) (p= 0.038). We did not find differences in the need for mechanical ventilation and mortality between patients who tolerated and who did not tolerate PP. From those 18 who tolerated PP, 10 were classified as responders (55,5%). We did not find any significant statistical differences for admission to ICU between responders and non-responders. PP in awake patients is a feasible tool in cases of COVID-19 Pneumonia, and it allowed us to predict the requirements of ICU between those who were not tolerant to the method.
Keywords: COVID-19; prone; awake; pneumonia; hypoxemia